La minería mexicana: el ocaso de un modelo nacionalista - Sariego Rodríguez, Juan Luis (2011)
In this paper, I discuss the central processes that have taken place in Mexican mining in the past two decades. In the international context of expanding markets and a boom in metal prices, the Mexican state, like others in Latin America, has chosen to liberalize concession laws supporting unconditionally the interests of Mexican mining monopolies and thus unleashing an onslaught of discrediting and dismantling of the miner’s Union. This mining industry growth model has resulted not only in mine worker protests, but also in demands of NGO’s, and Indigenous and other rural communities affected by environmental impacts of mining.